Tachornithoglyphus gen. nov.—a new genus of nidicolous Pyroglyphidae (Acariformes: Astigmata) - Klimov, Pavel B; Bochkov, Andre V; Oconnor, Barry M. (Zootaxa, 2015)
Tachornithoglyphus gen. nov. (Acariformes: Pyroglyphidae) is established for Tachornithoglyphus tachornis (Cruz, Cuervo and Dusbabek, 1984), comb. nov. (transferred from Guatemalichus), collected from nests of the Antillean palm swift, Tachornis phoenicobia (Apodiformes: Apodidae) in Cuba. The new genus differs from the other four genera of the subfamily Guatemalichinae, Guatemalichus Fain and Wharton, 1970, Pottocola Fain, 1971, Fainoglyphus Atyeo and Gaud, 1977, and Capitonocoptes Fain and Gaud, 1984, mainly by having the length of solenidion σ1 of genu I less than one-third that of the segment (vs. solenidion σ1I at least half as long as genu I), by the absence of famulus ε on tarsus I (vs. present), and by coxal apodemes Ia separated from each other and contiguous to the lateral parts of the epigynal arch (vs. posterior tips of apodemes Ia fused to each other and with the median part of the epigynal arch, or separated and contiguous to or fused with the median part of the epigynal arch). A detailed redescription of adults and tritonymphs of T. tachornis is provided.